A 2-Year, Phase IV, Multicentre, Observational Study of Ranibizumab 0.5 mg in Patients with Neovascular Age-Related Macular Degeneration in Routine Clinical Practice: The EPICOHORT Study. (28th April 2014) - Pagliarini, Sergio; Beatty, Stephen; Lipkova, Blandina; Perez-Salvador Garcia, Eduardo; Reynders, Stefaan; Gekkieva, Margarita; Si Bouazza, Abdelkader; Pilz, Stefan
Abstract : Purpose . To assess the safety profile of ranibizumab 0.5 mg in patients with neovascular age-related macular degeneration (nAMD) in routine clinical practice. Methods . This 2-year, multicentre, observational study was conducted to capture real-world early practice and outcomes across Europe, shortly after European licensing of ranibizumab for nAMD. Being observational in nature, the study did not impose diagnostic/therapeutic interventions/visit schedule. Patients were to be treated as per the EU summary of product characteristics (SmPC) in effect during the study. Key outcome measures were incidence of selected adverse events (AEs), treatment exposure, bilateral treatment, compliance to the EU SmPC, and best-corrected visual acuity (BCVA) over 2 years. Results . 755 of 770 patients received treatment. Ranibizumab was generally well tolerated with low incidence of selected AEs (0%–1.9%). Patients received 6.2 (mean) injections and 133 patients received bilateral treatment over 2 years. Protocol deviation to treatment compliance was reported in majority of patients. The observed decline in mean BCVA (Month 12, +1.5; Month 24, –1.3 letters) may be associated with undertreatment as suggested by BCVA subgroup analysis. Conclusion . The EPICOHORT study conducted in routine clinical practice reinforces the well-established safety profile of ranibizumab in nAMD. In early European practice it appeared that the nAMD patients were undertreated.